Bidirectional Regulation of Opioid and Chemokine Function - Rogers, Thomas J. (Frontiers in Immunology, 2020)
The opioid family of GPCRs consists of the classical opioid receptors, designated μ-, κ- and δ-opioid receptors, and the orphanin-FQ receptor, and these proteins are expressed on both neuronal and hematopoietic cells. A number of laboratories have reported that an important degree of cross-talk can occur between the opioid receptors and the chemokine and chemokine receptor families. As a part of this, the opioid receptors are known to regulate the expression of certain chemokines and chemokine receptors, including those that possess strong pro-inflammatory activity. At the level of receptor function, it is clear that certain members of the chemokine family can mediate cross-desensitization of the opioid receptors. Conversely, the opioid receptors are all able to induce heterologous desensitization of some of the chemokine receptors. Consequently, activation of one or more of the opioid receptors can selectively cross-desensitize chemokine receptors and regulate chemokine function. These cross-talk processes have significant implications for the inflammatory response, since the regulation of both the recruitment of inflammatory cells, as well as the sensation of pain, can be controlled in this way.